Advances in Optical Imaging for Pharmacological Studies - Alicia eArranz; Jorge eRipoll; Jorge eRipoll (Frontiers Media S.A., 2015)
Imaging approaches are an essential tool for following up over time representative parameters of in-vivo models, providing useful information in pharmacological studies. Main advantages of optical imaging approaches compared to other imaging methods are their safety, straight-forward use and cost-effectiveness. A main drawback, however, is having to deal with the presence of high scattering and high absorption in living tissues. Depending on how these issues are addressed, three different modalities can be differentiated: planar imaging (including fluorescence and bioluminescence in-vivo imaging), optical tomography, and optoacoustic approaches. In this review we describe the latest advances in optical in-vivo imaging with pharmacological applications, with special focus on the development of new optical imaging probes in order to overcome the strong absorption introduced by different tissue components, especially hemoglobin, and the development of multimodal imaging systems in order to overcome the resolution limitations imposed by scattering.